2014
DOI: 10.3389/fpsyg.2014.01411
|View full text |Cite
|
Sign up to set email alerts
|

Spatial navigation, episodic memory, episodic future thinking, and theory of mind in children with autism spectrum disorder: evidence for impairments in mental simulation?

Abstract: This study explored spatial navigation alongside several other cognitive abilities that are thought to share common underlying neurocognitive mechanisms (e.g., the capacity for self-projection, scene construction, or mental simulation), and which we hypothesized may be impaired in autism spectrum disorder (ASD). Twenty intellectually high-functioning children with ASD (with a mean age of ~8 years) were compared to 20 sex, age, IQ, and language ability matched typically developing children on a series of tasks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 72 publications
(101 reference statements)
4
41
0
Order By: Relevance
“…Deficits in working memory in ASD are also specific to increased working memory load, as increasing task complexity results in poorer performance (Kercood et al, 2014;Steele et al, 2007). Related to this, studies in children and adults with ASD have shown that spatial navigation ability is impaired (Lind et al, 2014;Lind et al, 2013).…”
Section: Learning and Memory Deficits In Asdmentioning
confidence: 96%
“…Deficits in working memory in ASD are also specific to increased working memory load, as increasing task complexity results in poorer performance (Kercood et al, 2014;Steele et al, 2007). Related to this, studies in children and adults with ASD have shown that spatial navigation ability is impaired (Lind et al, 2014;Lind et al, 2013).…”
Section: Learning and Memory Deficits In Asdmentioning
confidence: 96%
“…At the cognitive level, ASD is thought to be characterised by a particular profile of strengths and limitations in memory functioning (see individuals with ASD manifest impairments in both episodic memory, the ability to recall personally-experienced events, as well as episodic foresight, the ability to imagine events that are likely to be experienced in the future (Lind & Bowler, 2010;Lind, Bowler, & Raber, 2014;Lind, Williams, Bowler, & Peel, 2014;Terrett et al, 2013). Recent evidence has also indicated a substantial deficit in prospective memory, at least when spontaneous (as opposed to prompted) retrieval of prior intentions is required for successful completion of a planned action (see e.g., Altgassen, Koban, & Kliegel, 2012;Williams, Boucher, Lind, & Jarrold, 2013;Williams, Jarrold, Grainger, & Lind, 2014).…”
Section: Intention Superiority and Enactment Effects In Asdmentioning
confidence: 99%
“…These tests are, therefore, less realistic in terms of the real life navigation requirements than 3‐D environments. Such an environment is the island navigation task used by Lind et al [], where participants were asked to find target objects that were initially marked by clearly visible flags and then hidden to probe memory dependent spatial navigation. Lind et al [] observed that a group of ASD participants were less effective at finding the hidden objects despite having no difficulties reaching them when they were initially marked by the clearly visible flags.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the few previous studies that have investigated spatial navigation in ASD, however, report mixed findings. Some studies found no differences between groups [Edgin & Pennington, 2005;Caron, Mottron, Rainville, & Chouinard, 2004], some studies found an overall navigational deficit in ASD independent of whether conditions probed allocentric or egocentric skills [Lind, Williams, Raber, Peel, & Bowler, 2013], and a few studies found specific allocentric navigational difficulties as predicted [Prior & Hoffmann, 1990;Lind, Bowler, & Raber, 2014;Ring et al, 2018]. Only three of these earlier studies compared allocentric and egocentric conditions within one study [Lind et al, 2013Ring et al, 2018].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation